Common asymptomatic and submicroscopic malaria infections in Western Thailand revealed in longitudinal molecular and serological studies: a challenge to malaria elimination. (December 2016) - Baum, Elisabeth; Sattabongkot, Jetsumon; Sirichaisinthop, Jeeraphat; Kiattibutr, Kirakorn; Jain, Aarti; Taghavian, Omid; Lee, Ming-Chieh; Huw Davies, D.; Cui, Liwang; Felgner, Philip; Yan, Guiyun
Abstract Background Despite largely successful control efforts, malaria remains a significant public health problem in Thailand. Based on microscopy, the northwestern province of Tak, once Thailand's highest burden area, is now considered a low-transmission region. However, microscopy is insensitive to detect low-level parasitaemia, causing gross underestimation of parasite prevalence in areas where most infections are subpatent. The objective of this study was to assess the current epidemiology of malaria prevalence using molecular and serological detection methods, and to profile the antibody responses againstPlasmodium as it relates to age, seasonal changes and clinical manifestations during infection. Three comprehensive cross-sectional surveys were performed in a sentinel village and from febrile hospital patients, and whole blood samples were collected from infants to elderly adults. Genomic DNA isolated from cellular fraction was screened by quantitative-PCR for the presence ofPlasmodium falciparum, Plasmodium vivax, Plasmodium malariae, Plasmodium ovale andPlasmodium knowlesi. Plasma samples were probed on protein microarray to obtain antibody response profiles from the same individuals. Results Within the studied community, 90.2 % ofPlasmodium infections were submicroscopic and asymptomatic, including a large number of mixed-species infections. Amongst febrile patients, mixed-species infections comprised 68 % of positive cases, all of which went misdiagnosed and undertreated. All samples tested showed serological reactivity toPlasmodium antigens. There were significant differences in the rates of antibody acquisition againstP. falciparum andP. vivax, and age-related differences in species-specific immunodominance of response. Antibodies againstPlasmodium increased along the ten-month study period. Febrile patients had stronger antibody responses than asymptomatic carriers. Conclusions Despite a great decline in malaria prevalence, transmission is still ongoing at levels undetectable by traditional methods. As current surveillance methods focus on case management, malaria transmission in Thailand will not be interrupted if asymptomatic submicroscopic infections are not detected and treated.